Effects of bromelain and lyophilized pineapple juice on orthodontically induced root resorption in male guinea pigs a scanning electron microscopy study - Veleña, Harvenio Omar E., VI
General Objective: The aim of this investigation is to determine the effect of lyophilized pineapple juice and commercially available bromelain preparation on the root surface of guinea pigs during orthodontic tooth movement utilizing scanning electron microscopy.
Materials and Methods: Fifteen male guinea pigs were randomly assigned into three groups; control group, lyophilized pineapple juice extract group and bromelain preparation group. The orthodontic appliance used in this study comprised of 0.014-inch (0.035 mm) stainless steel formed into helical torsion spring which exerted an average force of 30± 1 grams. The test substance bromelain was given to the animals in two forms; bromelain preparation at a dosage of 7 mg/kg and lyophilized pineapple juice extract with a dosage of 30 mg/kg. After the experiment, the animals were sacrificed and the upper left incisors were extracted and dehydrated in a series of ethanol containers of increasing strength. Scanning Electron Microscope (SEM) was used to study the distal surfaces of the root specimens. Composite electron micrographs of the distal surfaces of guinea pigs roots at 15 x magnification were then used to measure the area occupied by the resorption lacunae and recorded as root resorption scores with the use of ImageJ® analysis software. Levene's Test of Equality of Error Variances tested the homogeneity of the variances. It was found out in that the variances are not homogenous; therefore ANOVA cannot be used in this analysis. Kruskal-Wallis test revealed that there are significant differences among groups and the control group is different from the experimental groups 1 and 2. The difference between groups 1 and 2 is not statistically significant.
Results: Among the three groups, the control group showed the highest root resorption score with the mean value of 29.63080 mm² and 4.24640 mm² respectively. The outcome revealed a statistically significant result (P-value < 0.004).
Conclusion: Based on the results of this research, it is evident that bromelain inhibited the progression of root resorption in the experimental animals.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontics; Teeth--Mobility.; Tooth--Movement.; Bromelain; Pineapple